2022
DOI: 10.3390/ijerph192417080
|View full text |Cite
|
Sign up to set email alerts
|

More than a Physical Problem: The Effects of Physical and Sensory Impairments on the Emotional Development of Adults with Intellectual Disabilities

Abstract: With the introduction of the ICD-11 and DSM-5, indicators of adaptive behavior, including social–emotional skills, are in focus for a more comprehensive understanding of neurodevelopmental disorders. Emotional skills can be assessed with the Scale of Emotional Development-Short (SED-S). To date, little is known about the effects of physical disorders and sensory impairments on a person’s developmental trajectory. The SED-S was applied in 724 adults with intellectual disabilities, of whom 246 persons had an add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Affective disorders could be seen across several levels of ED (Lytochkin et al 2021). Furthermore, no association of the level of ED and epilepsy could be seen in two different samples (Pena-Salazar et al 2021;Sterkenburg et al 2022).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Affective disorders could be seen across several levels of ED (Lytochkin et al 2021). Furthermore, no association of the level of ED and epilepsy could be seen in two different samples (Pena-Salazar et al 2021;Sterkenburg et al 2022).…”
Section: Discussionmentioning
confidence: 97%
“…In this study, affective disorders were not associated with lower levels of ED. Sterkenburg et al (2022) examined the effects of physical and sensory impairments on emotional functioning. Interestingly, movement disorders were associated with more severe ID and lower levels of ED on the overall level and on certain domains (others, body, material and communication).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, recent work (Sterkenburg et al . 2022) has shown that different physical and sensory impairments are related to specific domains of ED.…”
Section: Discussionmentioning
confidence: 99%
“…Hereby, comparison of the different scales on the domain level may be supportive to obtain better insights within the different aspects of ED. For instance, recent work (Sterkenburg et al 2022) has shown that different physical and sensory impairments are related to specific domains of ED.…”
Section: Discussionmentioning
confidence: 99%